Bacterial leaching of an Indonesian complex copper sulfide ore using an iron-oxidizing indigenous bacterium (Microbiology Indonesia, 2018)
The bioleaching of an Indonesian complex copper sulfide ore was studied in shake flasks over a period of 14 days using an iron-oxidizing indigenous bacterium at room temperature (28 oC) and various pulp densities (5% and 20%). The bioleaching suspensions were periodically analyzed for Cu and Fe concentrations as well as Eh, pH and DO values. Cu bioleaching efficiencies at 5% pulp density were higher than those at 20% pulp density, which correlated with Fe concentration in solution. Over a period of 14 days, the pH of bioleaching suspension was in the range of 5 ~ 9, indicating that Cu bioleaching was greatly influenced not only by proton H+ dan ferric ion but also by extracellular polymeric substances (EPS) generated by the bacterium. The current study may improve our better understanding on the bacterial action for bioleaching of complex copper sulfide ores that remains debated so far as refractory ores.